Optimisation of Itraconazole Therapy Using Target Drug Concentrations - Poirier, Marie; Cheymol, Georges (Clinical pharmacokinetics, 1998)
Itraconazole is a new triazole compound with a broad spectrum of activity against a number of fungal pathogens, including Aspergillus species. The drug is being used increasingly as prophylaxis in patients with immunodepression. Itraconazole is highly lipophilic and only ionised at low pH. The absolute availability of capsules in healthy volunteers under fasting conditions is about 55% and is increased after a meal. Itraconazole is 99.8% bound to human plasma proteins and its apparent volume of distribution is about 11 L/kg. The drug is extensively metabolised by the liver. Among the metabolites, hydroxy-itraconazole is of particular interest because its antifungal activity measured in vitro is similar to that of the parent drug and its plasma concentration is 2 to 3 times higher than that of itraconazole. Mean total itraconazole blood clearance determined in healthy volunteers following a single intravenous infusion was 39.6 L/h. After a single oral dose, the terminal elimination half-life of itraconazole is about 24 hours. The drug exhibits a dose-dependent pharmacokinetic behaviour. Renal failure does not affect the pharmacokinetic properties of itraconazole; however, little is known about the effects of hepatic insufficiency. In immunocompromised patients the absorption of itraconazole is affected by gastrointestinal disorders caused by diseases and cytotoxic chemotherapy. The pharmacokinetics of itraconazole may be significantly altered when the drug is coadministered with certain other agents. Itraconazole is a potent inhibitor of cytochrome P450 (CYP) 3A4 and, thus, can also considerably change the pharmacokinetics of other drugs. Such changes may have clinically relevant consequences. Itraconazole appears to be well tolerated. Gastrointestinal disturbances and dizziness are the most frequently reported adverse effects. Clinical studies in patients with haemotological malignancies suggest that plasma concentrations [measured by high performance liquid chromatography (HPLC)] > or = 250 micrograms/L itraconazole, or 750 to 1000 micrograms/L for itraconazole plus hydroxy-itraconazole, are required for effective prophylactic antifungal activity. It seems that a curative effect may be enhanced by ensuring that itraconazole plasma concentrations exceed 500 micrograms/L. The marked intra- and inter-patient variability in the pharmacokinetics of the drug, and the fact that it is impossible to predict steady-state plasma concentrations from the initial dosage are major factors obscuring any clear relationship between dose and plasma concentrations and clinical efficacy. Thus, in patients with life-threatening fungal infections treated with itraconazole drug, plasma concentrations should be regularly monitored to ensure sufficient drug exposure for antifungal activity.